2015
DOI: 10.1177/0022343314555782
|View full text |Cite
|
Sign up to set email alerts
|

Empowering activists or autocrats? The Internet in authoritarian regimes

Abstract: The reported role of social media in recent popular uprisings against Arab autocrats has fueled the notion of 'liberation technology', namely that information and communication technology (ICT) facilitates organization of antigovernment movements in autocracies. Less optimistic observers, on the other hand, contend that ICT is a tool of repression in the hands of autocrats, imposing further restrictions on political and social liberties. We investigate whether the liberation-or the repression-technology perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(95 citation statements)
references
References 38 publications
2
91
1
Order By: Relevance
“…Whether or how forms of political institutions, regime type, influence the government's Internet adoption or whether the government's Internet adoption affects its democratic process has been a topic of great interest in recent years Guillén and Suárez, 2005;Seo and Thorson, 2012;Kedzie, 1997;Milner, 2006;Norris, 2001;Rød and Weidmann, 2015. Empirical and theoretical studies in this area have presented somewhat conflicting arguments.…”
Section: Regime Type and Internet Adoptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Whether or how forms of political institutions, regime type, influence the government's Internet adoption or whether the government's Internet adoption affects its democratic process has been a topic of great interest in recent years Guillén and Suárez, 2005;Seo and Thorson, 2012;Kedzie, 1997;Milner, 2006;Norris, 2001;Rød and Weidmann, 2015. Empirical and theoretical studies in this area have presented somewhat conflicting arguments.…”
Section: Regime Type and Internet Adoptionmentioning
confidence: 99%
“…The first argues that there is a significant association between the type of political institution and the country's adoption of digital communication technologies such as the Internet with democratic countries being more likely to adopt the InternetGuillén and Suárez, 2005; Kedzie, 1997;Milner, 2006. In contrast, the second group argues that the Internet adoption does not always help a country become more open or democratic Rød and Weidmann, 2015. Examining data from roughly 200 countries from 1991 to 2001, Milner, 2006 found that political institutions significantly influenced the spread of the Internet even after controlling for alternative explanations such as economic development. In particular, Milner argued that regime type plays an important role in this with democracies adopting the Internet at a much faster pace than autocracies.…”
Section: Regime Type and Internet Adoptionmentioning
confidence: 99%
See 3 more Smart Citations